2009
DOI: 10.1021/jp810131f
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Measurements of Acetaldehyde on Solid Ice Surfaces and on Solid/Liquid Supercooled Mixtures Doped with HNO3 in the Temperature Range 203−253 K

Abstract: Uptake of acetaldehyde on ice surfaces has been investigated over the temperature range 203-253 K using a coated wall flow tube coupled to a mass spectrometric detection. The experiments were conducted on pure ice surfaces and on liquid/solid ice mixture both doped with nitric acid (0.063, 0.63, and 6.3 wt %). Uptake of acetaldehyde on these surfaces was always found to be totally reversible whatever the experimental conditions were. The number of acetaldehyde molecules adsorbed per surface unit was convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 36 publications
7
41
0
Order By: Relevance
“…Where the necessary data are available (parameterizations for Henry's Law constant, activity coefficient, and solubility in the ice matrix), organic species may be modeled in the same fashion as inorganic species. Related to this discussion are experiments by Petitjean et al (2009), which showed increased, solubility-driven uptake of acetaldehyde in the presence of HNO 3 under conditions where it may form a brine at the ice surface, consistent with observations for ethanol (Kerbrat et al, 2007) and acetone (Journet et al, 2005).…”
Section: Dissolution Into Brinesupporting
confidence: 86%
See 1 more Smart Citation
“…Where the necessary data are available (parameterizations for Henry's Law constant, activity coefficient, and solubility in the ice matrix), organic species may be modeled in the same fashion as inorganic species. Related to this discussion are experiments by Petitjean et al (2009), which showed increased, solubility-driven uptake of acetaldehyde in the presence of HNO 3 under conditions where it may form a brine at the ice surface, consistent with observations for ethanol (Kerbrat et al, 2007) and acetone (Journet et al, 2005).…”
Section: Dissolution Into Brinesupporting
confidence: 86%
“…It was also found to be independent of the state (i.e., liquid versus frozen) of the condensed phase; this was attributed to the presence of the DI. Comparable results have also been obtained with many other oxygenated VOC species, such as acetaldehyde (Petitjean et al, 2009), formic and acetic acids (Jedlovszky et al, 2008;Symington et al, 2010), and alcohols (Kerbrat et al, 2007;Abbatt et al, 2008). A few studies have also shown that the coadsorption of a VOC with another trace gas onto the ice surface can be described well using a competitive Langmuir adsorption model Kerbrat et al, 2010) in the absence of chemically-induced surface changes (McNeill et al, 2006).…”
Section: Molecular-level Picturementioning
confidence: 81%
“…2). At 243 K, a value of 3.8 pptw is found, because Petitjean et al (2009) observed of a very weak temperature dependence of acetaldehyde adsorption on ice around 240 K. Even with the approximations made on P CH3CHO , on temperature and on other variables, there is no reasonable scenario that can make the laboratory data of Petitjean et al (2009) agree with our field measurements, confirming that adsorption onto ice surfaces can only explain a negligible fraction of the acetaldehyde concentrations that we measured.…”
Section: Adsorption and Dissolution Hypothesessupporting
confidence: 41%
“…Despite the lack of data on P CH3CHO , we can nevertheless seek a confirmation of this conclusion from recent laboratory measurements of acetaldehyde adsorption on ice, at temperatures up to 253 K (Petitjean et al, 2009). We nevertheless need an estimation of P CH3CHO , which can be obtained from acetaldehyde measurements at Arctic locations.…”
Section: Adsorption and Dissolution Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation